Maternal sepsis: A Scottish population-based case-control study - Acosta, C; Bhattacharya, S; Tuffnell, D; Kurinczuk, J; Knight, M (2012)
Objective To describe the risk of maternal sepsis associated with obesity and other understudied risk factors such as operative vaginal delivery. Design Population-based, case-control study. Setting North NHS region of Scotland. Population All cases of pregnant, intrapartum and postpartum women with International Classification of Disease-9 codes for sepsis or severe sepsis recorded in the Aberdeen Maternal and Neonatal Databank (AMND) from 1986 to 2009. Four controls per case selected from the AMND were frequency matched on year-of-delivery. Methods Cases and controls were compared; significant variables from univariable regression were adjusted in a multivariable logistic regression model. Main outcome measures Dependent variables were uncomplicated sepsis or severe ('near-miss') sepsis. Independent variables were demographic, medical and clinical delivery characteristics. Unadjusted and adjusted odds ratios (OR) with 95% confidence intervals (95% CI) are reported. Results Controlling for mode of delivery and demographic and clinical factors, obese women had twice the odds of uncomplicated sepsis (OR 2.12; 95% CI 1.14-3.89) compared with women of normal weight. Age <25 years (OR 5.15; 95% CI 2.43-10.90) and operative vaginal delivery (OR 2.20; 95% CI 1.02-4.87) were also significant predictors of sepsis. Known risk factors for maternal sepsis were also significant in this study (OR for uncomplicated and severe sepsis respectively): multiparty (OR 6.29, 12.04), anaemia (OR 3.43, 18.49), labour induction (OR 3.92 severe only), caesarean section (OR 3.23, 13.35), and preterm birth (OR 2.46 uncomplicated only). Conclusions Obesity, operative vaginal delivery and age <25 years are significant risk factors for sepsis and should be considered in clinical obstetric care. © 2012 RCOG.